Renal Tuberculosis: A Case History that makes or Breaks the Case, Nothing is more Deceptive - Khan, Urvashi; Jha, LK; Tyagi, Pranav; Sharma, Aditya; Maggon, Rita Rani; Pandey, Neha (Journal of Clinical Nephrology, 2024)
This manuscript presents a compelling case of renal tuberculosis in a 15-year-old male, elucidating the intricate diagnostic hurdles and strategic management approaches encountered. The patient initially presented with nonspecific symptoms, including intermittent low-grade fever, weight loss, fatigue, and diffuse skin rashes, which were initially managed as suspected enteric fever. However, as the patient’s condition deteriorated, a comprehensive diagnostic exploration revealed renal tuberculosis. The report meticulously outlines the clinical presentation, diagnostic evaluation, and therapeutic trajectory, emphasizing the enigmatic nature of symptoms and advocating for a multidimensional diagnostic paradigm integrating clinical, radiological, microbiological, and histopathological assessments. Furthermore, this case report provides a comprehensive review of urogenital tuberculosis, discussing its epidemiological underpinnings, clinical manifestations, diagnostic methodologies, and therapeutic tenets. It underscores the paramount significance of early recognition and prompt initiation of treatment in forestalling complications and optimizing patient outcomes. This case report enriches the medical discourse by shedding light on the diagnostic intricacies and therapeutic imperatives pertinent to renal tuberculosis, especially in the younger demographic. We believe that the findings will contribute significantly to the understanding and management of this disease.